ANALISIS KINERJA BERBASIS KOMUNIKASI KEPEMIMPINAN DAN GAYA KEPEMIMPINAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - wicaksono Yuni Ardhi Santoso (UPAJIWA, 2019)
This research aims to know: (1) influence of leadership communication toward employee’s motivation and performance (3) influence of leadership style toward employee’s motivation and performance (5) influence of motivation toward employee’s performance at BUKP DIY of Bantul Regency. This research was explanatory research by using quantitative approach. Population of the research was all employees of BUKP DIY in Bantul Regency as total of 77 people. Sampling technique in this research was by non-probability sampling model with number of sample was 77 people. Data collection was by questionnaire. Data analysis used SEM analysis. Result of the research shows that: (1) leadership communication has positive and significant influence toward employee’s motivation and performance (2) leadership style has positive and significant influence toward employee’s motivation and performance (3) motivation has positive and significant influence toward employee’s performance at BUKP DIY of Bantul Regency. Keywords: leadership communication, leadership style, employee;s motivation and employee’s performance